Study of the isomeric yield ratio in the photoneutron reaction of natural holmium induced by laser-accelerated electron beams - Zhang, Jingli; Qi, Wei; Fan, Wenru; Cao, Zongwei; Luo, Kaijun; Tan, Changxiang; Zhang, Xiaohui; Deng, Zhigang; Zhang, Zhimeng; Li, Xinxiang; Yuan, Yun; Luo, Wen; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Introduction: An accurate knowledge of the isomeric yield ratio (IR) induced by the photonuclear reaction is crucial to study the nuclear structure and reaction mechanisms. 165Ho is a good candidate for the investigation of the IR since the Ho target has a natural abundance of 100% and the residual nuclide has a good decay property. Methods: In this study, the photoneutron production of 164m, gHo induced by laser-accelerated electron beams is investigated experimentally. The γ-ray spectra of activated Ho foils are off-line detected. Since the direct transitions from the 164mHo are not successfully observed, we propose to extract the IRs of the 164m, gHo using only the photopeak counts from the ground-state decay. Results: The production yields of 164m, gHo are extracted to be (0.45 ± 0.10) × 106 and (1.48 ± 0.14) × 106 per laser shot, respectively. The resulting IR is obtained to be 0.30 ± 0.08 at the effective γ-ray energy of 12.65 MeV. Discussion: The present data, available experimental data, and TALYS calculations are then compared to examine the role of the excitation energy. It is found that besides the giant dipole resonance, the excitation energy effect also plays a key role in the determination of the IRs.